Lower extremity isokinetic strength characteristics of amateur boxers - Zhou, Zixiang; Chen, Chao; Chen, Xin; Yi, Wenjuan; Cui, Weijia; Wu, Rui; Wang, Dexin (Frontiers in Physiology, 2022)
Aim: Sufficient strength and dynamic stability of the lower limbs are essential for improving punching force and preventing injury in amateur boxers. However, there are still no comprehensive reports on the isokinetic knee strength of boxers with different performance levels. The current study aimed to profile the isokinetic muscle strength of flexion and extension of the knee in boxers, as well as bilateral, unilateral, and functional ratios, and investigate the variation in these muscle strength characteristics associated with different performance levels. Methods: Boxers were divided in two performance groups, elite (five males and four females) and non-elite groups (five males and four females). Muscle strength of the knee was determined via an IsoMed2000 device. Parameters examined included peak torque of the hamstring (H) and quadriceps (Q) during concentric (con) and eccentric (ecc) contractions at low (60°/S), medium (180°/S), and high (240°/S) speed and bilateral ratios (BLs), unilateral ratios (ULs), and functional ratios of dominant (D) and non-dominant limbs. Results: In all angular velocities, the peak torque of H and Q was stronger in the elite group than in the non-elite group. ULs were lower in the elite group than in the non-elite group in Hcon/Qcon at 180D (p < 0.01) and 180ND (p < 0.05) and in Hecc/Qecc at 60D, 180D (p < 0.05) and 240D (p < 0.01). The elite group had higher BLs than the non-elite group in Hcon at 60°/S (p < 0.05) and Qcon at 180°/S (p < 0.05). The non-elite group had a higher functional ratio than elite boxers in Hecc/Qcon at 180D and 240D (p < 0.01). Conclusion: Elite boxers had stronger knee strength in con and ecc contractions. All boxers had normal Hecc/Qecc and Hcon/Qecc. Hcon/Qcon and Hecc/Qcon were abnormal at lower angular velocity. Elite boxers had higher BLs and lower ULs, indicating that they are at a higher risk of injury.